2015
DOI: 10.1111/bdi.12336
|View full text |Cite
|
Sign up to set email alerts
|

A reduced risk of stroke with lithium exposure in bipolar disorder: a population‐based retrospective cohort study

Abstract: Lithium use was significantly related to a reduced risk of stroke in patients with bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 45 publications
2
47
0
1
Order By: Relevance
“…Therefore, patients at risk for stroke with unfortunate collateral status (thus portending poor outcome) could particularly profit from a lithium treatment at low concentrations via a generally improved endothelium-dependent vessel relaxation capacity. This might be speculative, but on the other hand, the lithium-augmented cerebrovascular relaxation capacity may party explain, why continuous lithium treatment can reduce the risk for stroke (Lan et al, 2015) or may improve neurologic recovery after cortical stroke (Mohammadianinejad et al, 2014) potentially caused by various beneficiary effects on neurons (Doeppner et al, 2016; Vosahlikova and Svoboda, 2016), or platelets (Barry et al, 2003) including the direct ones on vascular and cerebrovascular endothelium (Afsharimani et al, 2007; Rahimzadeh-Rofouyi et al, 2007; Bosche et al, 2013, 2016), as presented here. Directly or secondarily impaired endothelial barrier after ischemia and hemorrhages followed by vasogenic edema formation (Stokum et al, 2016) were known to be highly relevant for clinical outcome of various types of stroke (Hacke et al, 1996; Bosche et al, 2003; Macdonald, 2014; Wijdicks et al, 2014; Urday et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, patients at risk for stroke with unfortunate collateral status (thus portending poor outcome) could particularly profit from a lithium treatment at low concentrations via a generally improved endothelium-dependent vessel relaxation capacity. This might be speculative, but on the other hand, the lithium-augmented cerebrovascular relaxation capacity may party explain, why continuous lithium treatment can reduce the risk for stroke (Lan et al, 2015) or may improve neurologic recovery after cortical stroke (Mohammadianinejad et al, 2014) potentially caused by various beneficiary effects on neurons (Doeppner et al, 2016; Vosahlikova and Svoboda, 2016), or platelets (Barry et al, 2003) including the direct ones on vascular and cerebrovascular endothelium (Afsharimani et al, 2007; Rahimzadeh-Rofouyi et al, 2007; Bosche et al, 2013, 2016), as presented here. Directly or secondarily impaired endothelial barrier after ischemia and hemorrhages followed by vasogenic edema formation (Stokum et al, 2016) were known to be highly relevant for clinical outcome of various types of stroke (Hacke et al, 1996; Bosche et al, 2003; Macdonald, 2014; Wijdicks et al, 2014; Urday et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also identified protective effects of lithium in cardiovascular and cerebrovascular diseases (Gold et al, 2011; Chiu and Chuang, 2012). This protective effect was highlighted by two recent clinical studies demonstrating that prolonged lithium treatment reduces the risk of ischemic stroke in bipolar disorder patients (Lan et al, 2015), and improves neurological recovery after cortical stroke (Mohammadianinejad et al, 2014). Stroke and thromboembolism risk depend not only on cerebral but also on general endothelial functioning.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The reduced risk was also correlated with a higher dose, longer treatment duration and a higher rate of exposure to lithium 794. In the second study, in a sample of 4729 patients diagnosed with BD, lithium exposure was associated with a reduced risk of cancer, compared to a group prescribed anticonvulsant medications.…”
Section: Specific Populationsmentioning
confidence: 91%
“…In einer ergänzenden Übersichtsarbeit, die auf kontrollierten klinischen Studien basiert, konnten für Lithium positive Effekte auf kognitive Funktionen beim amnestischen Typ der leichten kognitiven Störung sowie bei der Alzheimer-Demenz dargestellt werden [32]. In einer populationsbasierten Kohortenstudie zeigte sich zudem, dass Lithium offensichtlich das bei Bipolaren Störungen erhöhte Schlaganfallrisiko senkt, wobei die Risikoreduktion mit der Dauer und Dosis der Lithiumtherapie positiv korrelierte [33]. Bei insgesamt sehr spärlicher Datenlage scheint Lithium dagegen am ehesten keinen positiven Effekt auf andere neurodegenerative Erkrankungen wie Morbus Parkinson, Multisystematrophie, Amyotrophe Lateralsklerose und Morbus Huntington auszuüben [31,32].…”
Section: Neuroprotektionunclassified